Community service experience among employees at Pejabat Tanah Hulu Terengganu / Hajar Atiqah Azmi - Azmi, Hajar Atiqah (2014)
This study aims to examine the effect of community service experience among employees. There were 60 questionnaires distributed at Pejabat Tanah Hulu Terengganu and only 52 questionnaires were returned. Based on the article that was published by New Straits Times on September 12, 2012, Akil and Lingan reported that the Ministry of Education, Tan Sri Muhyiddin Yassin announced that every primary and secondary school will be required by 2017 to participate in community service in order to develop values-driven Malaysians. The research design used is descriptive research. This study used the Statistical Package for the Social Sciences (SPSS) version 20.0 for the data analysis. There are two factors have been tested in this study which are Community Service Experience and Satisfaction after Community Service. The respondents of this study were the staff of Pejabat Tanah Hulu Terengganu. From the findings, it can be concluded that majority employees have experiences in community service programs.